Nelineāras plaisu problēmas ar pielietojumiem kompozītos un ģeomehānikā - Tarasovs, Sergejs (Latvijas Universitāte, 2008)
The solution of non-linear problems in mechanics is usually a complex task. It requires much more e¤orts in analytical and numerical part of the solution (pure analytical solution for most problems is not possible at all). This work comprises solutions of several non-linear problems involving cracks growth and fractures. In the rst part of the work experimental procedure was elaborated in order to nd delamination properties of the unidirectional and translaminar-reinforced composites. Bridging law, which can be calculated from experimental data, is found to be important material property. Simple numerical procedure, which uses previously found bridging law, is proposed in order to simulate crack growth in composite laminates. In second part the three-dimensional mathematical model for analysis of Hot Dry Rock geothermal reservoirs is presented. By utilizing Laplace integral transform and Green s function the solution is reduced to integral equation over the surface of the fracture, which eliminates the need for discretizing the unbounded 3D reservoir. Using presented model temperature and thermally induced stresses can be found anywhere in the reservoir at any time, which makes this model quite e¢ cient in geothermal reservoirs analysis.
Nonlinear crack problems with application to composites and geomechanics
Elektroniskā versija nesatur pielikumus
Keywords: Fizika, astronomija un mehānika; Fizika; Fizika, materiālzinātne, matemātika un statistika